Labeling and Qualification of Endothelial Progenitor Cells for Tracking in Tissue Engineering: An in Vitro Study. Issue 4 (April 2015) - Thébaud, Noélie B.; Aussel, Audrey; Siadous, Robin; Toutain, Jérome; Bareille, Reine; Montembault, Alexandra; David, Laurent; Bordenave, Laurence
Purpose: In order to track location and distribution of endothelial cells (ECs) within scaffolds in vitro, we chose lentiPGK-TdTomato transduction of human endothelial progenitor cells (EPCs) isolated and differentiated from cord blood. Because transduction could have a functional impact on cell behavior, we checked different parameters for qualification of labeled- EPCs as well as their use for potential applications in the context of vascular and bone tissue engineering. Methods: After isolation and expansion, EPCs were classically characterized then transduced with the lentiviral vector containing the TdTomato protein gene under the control of the phosphoglycerate kinase (PGK) promoter. Conventional karyotyping, differentiation capacity, viability, proliferation assays were performed with labeled and unlabeled EPCs. Scaffolds and co-cultures were explored with labeled EPCs, in static or shear stress conditions. Results: Our results show that cell labeling did not affect cell adhesion nor induce cell death. Cell labeling did not induce more chromosomal aberrations. Phenotypical characterization was not affected. In the context of tissue engineering applications, labeled EPCs maintained their ability to line 2D or 3D scaffolds, withstand physiological arterial shear stress, and form tubular networks in co-cultures with human osteoblast progenitor cells. Conclusions: It is possible to label human EPCs with TdTomato without affecting their behavior by the transduction procedure. This creates an important tool for numerous applications. Our results provide a qualification of labeled EPCs in comparison with unlabeled ones for vascular and bone tissue engineering.